Ethnographic Study: The Choice of Place and Birth Attendants from the Socio-Cultural Perspective in the Tunjung Benuaq Dayak Tribe - Oktaviana, Lydia; Prasetyo, Budi; Izzati, Dwi; Djuari, Lilik (Universitas Muhammadiyah Sidoarjo, 2024)
WHO recommends Skill Birth Attendants (SBA) for all births. Around 50 million mothers in developing countries give birth at home without the help of medical personnel. The trust in traditional birth attendants (TBA), meaning that social and cultural influences still strongest. Objective: to analyze the choice of place and birth attendants in the Tunjung Benuaq Dayak Tribe through a socio-cultural perspective in the working area of the Barong Tongkok Community Health Center. Methodology: Qualitative Design with Ethnographic study using the Rapid Ethnographic Assessment Procedure (REAP) method. Snowball sampling is a variation of Purposive Sampling. In-depth interviews were conducted with 12 informants. Data analysis uses Thematic analysis. Results: The Tunjung Benuaq Dayak tribe upholds the values of balance and harmonization regarding human relationships with God, human and the environment. They developed local cultures based on complementary belief systems. There is a positive acceptance of science. The local wisdom of Santaap, eating a small portion of the food served, illustrates that they can accept little of knowledge. Customs are still maintained in the birthing process which is carried out by village shamans who are highly trusted by the community. They make the rituals, belief in myths (tempuunt), the existence of spirits who guard and interfere with the birthing process. Conclusion: Socio-cultural values such as trust, knowledge, and customs are very strong guidelines for the Tunjung Benuaq Dayak tribe in choosing a place and birth attendant. Suggestion: preservation of culture and customs that are still considered good in childbirth practices is highly desirable.